Lactobacillus plantarum attenuates glucocorticoid-induced osteoporosis by altering the composition of rat gut microbiota and serum metabolic profile - Li, Siying; Han, Xuebing; Liu, Naiyuan; Chang, Jiang; Liu, Gang; Hu, Siwang (Frontiers in Immunology, 2024)
Osteoporosis, one of the most common non-communicable human diseases worldwide, is one of the most prevalent diseases of the adult skeleton. Glucocorticoid-induced osteoporosis (GIOP) is the foremost form of secondary osteoporosis, extensively researched due to its prevalence. Efforts have been dedicated to identifying therapeutic agents that are efficacious yet devoid of side effects. Probiotics constitute a primary bioactive component within numerous foods, offering promise as a potential biological intervention for preventing and treating osteoporosis. This study aimed to evaluate the beneficial effects of the probiotic Lactobacillus plantarum on bone health and its underlying mechanisms in a rat model of glucocorticoid dexamethasone-induced osteoporosis, using the osteoporosis treatment drug alendronate as a reference. We examined the bone microstructure and analyzed the gut microbiome and serum metabolome in rats. The results revealed that L. plantarum treatment significantly restored parameters of bone microstructure, with elevated bone density, increased number and thickness of trabeculae, and decreased trabecular separation. Gut microbiota sequencing results showed that probiotic treatment increased gut microbial diversity and the ratio of Firmicutes to Bacteroidota decreased. Beneficial bacteria abundance was significantly increased (Lachnospiraceae_NK4A136_group, Ruminococcus, UCG_005, Romboutsia, and Christensenellaceae_R_7_group), and harmful bacteria abundance was significantly decreased (Desulfovibrionaceae). Serum metabolites changed significantly in different groups. These differential metabolites were predominantly enriched within the pathways of Pentose and Glucuronate Interconversions, as well as Propanoate Metabolism. Furthermore, treatment of L. plantarum significantly increased serum levels of Pyrazine and gamma-Glutamylcysteine, which were associated with inhibition of osteoclast formation and promoting osteoblast formation. In conclusion, Lactobacillus plantarum can protect rats from DEX-induced GIOP by mediating the "gut microbial-bone axis"promoting the production of beneficial bacteria and metabolites.Therefore L. plantarum is a potential candidate for the treatment of GIOP.